Influence of structural and material properties of GCLs on interface flow in composite liners due to geomembrane defects. Issue 1 (February 2010) - Mendes, M.J.A.; Touze-Foltz, N.; Palmeira, E.M.; Pierson, P.
Abstract : ABSTRACT: The flow rates along the interface between damaged geomembranes (GM) and geosynthetic clay liners (GCL) placed on top of a compacted clay liner (CCL) were measured by means of laboratory tests performed with an apparatus especially designed for this purpose. The tests performed were aimed at verifying the influence of the structural and material properties of the GCL on the transmissivity along the GM–GCL interface and flow rates through composite liners. Four types of GCLs with two different bonding processes (stitch-bonded or needle-punched) and different bentonites (natural sodium or natural calcium) were tested. The results obtained showed no significant differences among flow rate versus time in most of the tests performed, especially after the steady-state conditions of flow were reached. An analytical solution was employed to estimate the transmissivity of the GM–GCL interfaces. This solution also allowed predictions of flow rates and radius of wetted areas for typical configurations of composite liners in the field. The results obtained showed little influence of the nature of the bentonite and the predominance of the presence of preferential flow paths between the geomembrane and the GCL surface on the transmissivity of GM–GCL interfaces and flow rates through composite liners.